Capsule type metal catalyst as well as preparation method and application thereof

By preparing capsule metal catalysts, combining sodium carboxymethylcellulose, gelatin and nano-scale oxides, the problems of selectivity and product separation of traditional catalysts in the hydrosilic acid addition reaction are solved, and efficient and selective catalysis is achieved Effect.

CN119425812AActive Publication Date: 2025-02-14YUNNAN PRECIOUS METALS LAB CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411522050.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The traditional Karstedt catalyst has problems such as insufficient selective activation, difficulty in separation of reaction products and by-products in the hydrosil addition reaction between olefins and silanes, which limits its industrial application.

Method used

Using the preparation method of capsule metal catalyst, by combining metal salts (such as Pt, Pd or Ru) with materials such as carboxymethylcellulose sodium and gelatin, nanoscale silica or titanium dioxide as additives, through composite gel method Capsule-type catalysts with high catalytic activity and target product selectivity were prepared.

Benefits of technology

It has achieved efficient catalyzing of hydrosil addition reaction reaction between olefins and silanes under mild reaction conditions, which has improved the reactant conversion rate and the selectivity of the target product, and has a wider applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108270420000131
    Figure BDA0005108270420000131
  • Figure BDA0005108270420000141
    Figure BDA0005108270420000141
  • Figure HDA0005108270430000011
    Figure HDA0005108270430000011
Patent Text Reader

Abstract

The invention provides a capsule type metal catalyst and a preparation method and application thereof, and the preparation method comprises the following steps: (1) preparing a sodium carboxymethyl cellulose aqueous solution with a certain concentration, adding an additive and a metal salt solution, and uniformly dispersing to obtain a mixed solution A; (2) preparing a gelatin aqueous solution with a certain concentration, then uniformly mixing the gelatin aqueous solution with the mixed solution A, adjusting the pH value of the solution to be acidic, and continuing the reaction to obtain a mixed solution B; (3) placing the obtained mixed solution B in an ice-water bath, and adding a curing agent to carry out a cross-linking curing reaction to obtain a material C; and (4) washing and drying the material C to obtain the capsule type metal catalyst. The capsule type metal catalyst prepared by the invention is applied to hydrosilylation reaction, and can realize high reactant conversion rate and high target product selectivity under mild reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a capsule-type metal catalyst and a preparation method and application thereof. Background Art

[0002] The platinum (Pt)-catalyzed hydrosilylation reaction of olefins and silanes has important industrial applications in the field of homogeneous catalysis. This reaction converts basic olefins and silanes into high-value-added silicon-based materials, which have a wide range of applications in adhesives, coatings, drug development, etc. For example, (n-octyl)Si(OEt) 3 The annual output of Karstedt catalyst exceeds 6,000 tons. By using multifunctional olefins as reaction substrates, hydrosilylation products containing one or more functional groups can be synthesized, further broadening its application range. However, the traditional Karstedt catalyst cannot selectively activate substrate molecules, which often makes it difficult to separate the reaction products or produces unnecessary by-products, limiting its industrialization process. Although some catalysts can improve catalytic activity under specific conditions, they usually require harsh reaction conditions, have limited selectivity, and are not widely applicable.

[0003] In summary, it is necessary to develop a new and efficient metal catalyst and its preparation method to overcome the above problems, which is of great significance to the field of organosilicon chemical industry. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a capsule-type metal catalyst for hydrosilylation reaction with mild reaction conditions, good catalytic activity, high reactant conversion rate and high target product selectivity, as well as a preparation method and application thereof.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a capsule-type metal catalyst comprises the following steps:

[0007] (1) preparing a sodium carboxymethyl cellulose aqueous solution of a certain concentration, and then adding an additive and a metal salt solution to the sodium carboxymethyl cellulose aqueous solution, and dispersing them uniformly to obtain a mixed solution A;

[0008] (2) preparing a gelatin solution of a certain concentration, and mixing the gelatin solution and the mixed solution A uniformly, adjusting the pH of the solution to acidic and continuing the reaction to obtain a mixed solution B;

[0009] (3) placing the mixed solution B obtained in step (2) in an ice water bath, and adding a curing agent to carry out a cross-linking curing reaction to obtain material C;

[0010] (4) The material C is washed and dried to obtain the capsule-type metal catalyst.

[0011] The present invention is further configured such that, in step (1), the additive is selected from one or more of nano-sized silicon dioxide and nano-sized titanium dioxide; and the metal salt solution is selected from one of Pt, Pd or Ru metal salt alcohol solutions.

[0012] The present invention is further configured such that, in step (1), the metal salt of Pd is selected from at least one of sodium chloropalladate, palladium chloride or palladium nitrate dihydrate; the metal salt of Pt is selected from at least one of chloroplatinic acid hexahydrate, potassium tetrachloroplatinate or tetraammineplatinum dichloride; and the metal salt of Ru is selected from at least one of ruthenium chloride, ruthenium nitrate or hexaammineruthenium chloride.

[0013] The present invention is further configured such that the mass ratio of sodium carboxymethyl cellulose to gelatin is 0.4 to 3.0, and more preferably 0.75 to 2.0.

[0014] The present invention is further configured such that the added amount of the metal salt is 0.2 to 1.5 times the total mass of the sodium carboxymethyl cellulose and gelatin.

[0015] The present invention is further configured such that the mass of the additive is 0.006 to 0.2 times the mass of the metal salt.

[0016] The present invention is further configured such that in step (2), after the gelatin aqueous solution and the mixed solution A are uniformly mixed, the pH of the solution is adjusted to acidic and then the reaction is continued to obtain a mixed solution B; wherein the temperature of the reaction system is 40 to 60°C, the pH of the solution is adjusted to 3.8 to 4.7, and the reaction time is 0.5h to 3.0h. Preferably, the pH of the solution is adjusted to 4.0 to 4.5; more preferably, the pH of the solution is adjusted to 4.1.

[0017] The present invention is further configured such that the mass concentration of the sodium carboxymethyl cellulose aqueous solution is 1 to 10 wt %, more preferably 1 to 5 wt %; the mass concentration of the gelatin aqueous solution is 1 to 10 wt %, more preferably 1 to 5 wt %.

[0018] The present invention is further configured such that, in step (3), the curing agent is selected from at least one of glycerol and hydroxyethyl cellulose.

[0019] The present invention is further configured such that the added amount of the curing agent is 0.5 to 10 times the total mass of sodium carboxymethyl cellulose and gelatin; more preferably, 1 to 6 times.

[0020] The present invention is further configured such that, in step (3), the curing and cross-linking reaction time is 4 to 10 hours.

[0021] The present invention is further configured such that, in step (4), the solvent selected for washing is ethanol or acetone; and the drying conditions are: -20°C to 80°C, freeze drying for 8 to 20 hours.

[0022] The present invention also provides a capsule-type metal catalyst prepared according to the preparation method, wherein the metal loading amount is 0.05-2.0wt%.

[0023] The present invention also provides an application of the capsule-type metal catalyst for hydrosilylation reaction.

[0024] The present invention is further configured such that the capsule-type metal catalyst is used for the hydrosilylation reaction of ethylene and trimethoxysilane to prepare ethyltrimethoxysilane.

[0025] The present invention is further configured such that the conditions for the hydrosilylation reaction are: temperature 30-60° C., pressure: 0.25-0.5 MPa; more preferably, the reaction temperature is 35-55° C., and the pressure is 0.3-0.45 MPa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention provides a method for controllably preparing a capsule-type metal catalyst with an orderly and stable structure. Gelatin and sodium carboxymethyl cellulose are used as the wall materials of the catalyst, and an aqueous solution of gelatin and carboxymethyl cellulose is prepared. Nano-sized titanium dioxide or nano-sized silicon dioxide and a metal salt solution are added as additives. The capsule-type metal catalyst is prepared by a composite gel method. Different types of capsule-type metal catalytic materials are prepared by adjusting the proportion and elements of the metal salt, thereby achieving controllable preparation of different types of capsule-type metal materials.

[0028] (2) The capsule-type metal catalyst of the present invention encapsulates a homogeneous metal catalyst in a capsule, which is not only convenient for the transportation and storage of the catalyst, but also can stably release components with catalytic activity under mild reaction conditions; this capsule-type metal catalyst provides an ideal choice for the hydrosilylation reaction of silane molecules and olefin molecules due to its high catalytic activity and good target product selectivity.

[0029] (3) The catalyst of the present invention is applied to the hydrosilylation reaction of ethylene and trimethoxysilane to prepare ethyltrimethoxysilane, which can achieve excellent catalytic effect under relatively mild reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the capsule-type metal catalyst in Example 1. DETAILED DESCRIPTION

[0031] The present invention is described in detail and completely with specific embodiments and in conjunction with the accompanying drawings. It should be understood that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0032] As used herein, "room temperature" refers to 10-30°C, preferably 20-25°C.

[0033] The present invention provides a method for preparing a capsule-type metal catalyst, comprising the following steps:

[0034] (1) preparing a sodium carboxymethyl cellulose aqueous solution of a certain concentration at 40 to 60° C., then adding additives and a metal salt solution to the sodium carboxymethyl cellulose aqueous solution, and dispersing them uniformly to obtain a mixed solution A;

[0035] (2) preparing a gelatin solution of a certain concentration at 40 to 60° C., and uniformly mixing the gelatin solution and the mixed solution A, adjusting the pH of the solution to acidic and continuing the reaction to obtain a mixed solution B;

[0036] (3) placing the mixed solution B obtained in step (2) in an ice water bath, and adding a curing agent to carry out a cross-linking curing reaction to obtain material C;

[0037] (4) washing and drying the material C to obtain the capsule-type metal catalyst;

[0038] Wherein, in step (1), the additive is selected from one or more of nano-sized silicon dioxide and nano-sized titanium dioxide; the metal salt solution is selected from one of Pt, Pd or Ru metal salt alcohol solutions; in step (3), the curing agent is selected from at least one of glycerol and hydroxyethyl cellulose; the mass ratio of sodium carboxymethyl cellulose to gelatin is 0.4 to 3.0; the amount of the metal salt added is 0.2 to 1.5 times the total mass of sodium carboxymethyl cellulose and gelatin; the mass of the additive is 0.006 to 0.2 times the mass of the metal salt.

[0039] In one embodiment of the present invention, the mass ratio of sodium carboxymethyl cellulose to gelatin is 0.75-2.0, for example, 0.75, 1.0, 1.5 or 2.0.

[0040] In one embodiment of the present invention, the added amount of the metal salt is 0.5 to 1.2 times the total mass of sodium carboxymethyl cellulose and gelatin; more preferably 0.5 to 1.0 times.

[0041] In one embodiment of the present invention, in step (1), the metal salt of Pd is selected from at least one of sodium chloropalladate, palladium chloride or palladium nitrate dihydrate; the metal salt of Pt is selected from at least one of chloroplatinic acid hexahydrate, potassium tetrachloroplatinate or tetraammineplatinum dichloride; the metal salt of Ru is selected from at least one of ruthenium chloride, ruthenium nitrate or hexaammineruthenium chloride.

[0042] The concentration of the metal salt alcohol solution can be conventionally prepared by those skilled in the art according to needs. In one embodiment of the present invention, the concentration of the metal salt solution ranges from 0.5 mmol / L to 2 mmol / L.

[0043] In one embodiment of the present invention, in step (2), the gelatin solution and the mixed solution A are mixed evenly, the pH of the solution is adjusted to acidic and then the reaction is continued to obtain a mixed solution B; wherein the temperature of the reaction system is 40 to 60°C, the pH of the solution is adjusted to 3.8 to 4.7, and the reaction time is 0.5h to 3.0h.

[0044] In one embodiment of the present invention, the pH of the solution is adjusted to 4.0-4.5, for example, the pH of the solution is adjusted to 4.0, 4.1, 4.2, 4.3, 4.4 or 4.5.

[0045] In one embodiment of the present invention, the amount of the curing agent added in step (3) is 0.5 to 10 times the total mass of sodium carboxymethyl cellulose and gelatin, and more preferably 1 to 6 times.

[0046] In one embodiment of the present invention, in step (3), the curing and cross-linking reaction time is 4 to 10 hours.

[0047] In one embodiment of the present invention, in step (4), the solvent used for washing is ethanol or acetone; the drying conditions are: -20°C to 80°C, freeze drying for 8 to 20 hours.

[0048] The present invention also provides a capsule-type metal catalyst prepared according to the above preparation method, wherein the metal loading is 0.05-2.0 wt %, and more preferably 0.1-1.5 wt %.

[0049] The present invention also provides an application of the capsule-type metal catalyst for hydrosilylation reaction.

[0050] In one embodiment of the present invention, the capsule-type metal catalyst is used for catalytic performance of preparing ethyltrimethoxysilane by hydrosilylation reaction of ethylene and trimethoxysilane.

[0051] In one embodiment of the present invention, the conditions for the hydrosilylation reaction are: temperature 30-50°C, pressure: 0.25-0.5 MPa; more preferably, the temperature is 35-50°C, for example 35°C, 40°C, 45°C and 50°C; the pressure is preferably 0.3-0.45 MPa.

[0052] The technical solution of the present invention is described in detail below in conjunction with more specific embodiments.

[0053] Example 1

[0054] A method for preparing a capsule-type metal catalyst comprises the following steps:

[0055] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, then adding 0.02 g of nano-scale silicon dioxide and a chloroplatinic acid hexahydrate isopropanol solution containing 1.328 g of chloroplatinic acid hexahydrate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0056] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, and continuing to stir at 45° C. to obtain a mixed solution B. After adjusting the solution pH to 4.1, continue stirring and reacting for 75 minutes, and then obtain a mixed solution B.

[0057] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0058] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. The scanning electron microscopy image of the capsule-type metal catalyst is as follows: Figure 1 As shown, the prepared capsule-type metal catalyst was subjected to an inductively coupled plasma (ICP) test, and the Pt loading of the catalyst was 0.51 wt %.

[0059] Example 2

[0060] A method for preparing a capsule-type metal catalyst comprises the following steps:

[0061] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.005 g of nano-scale silicon dioxide and a dichlorotetraamineplatinum isopropanol solution containing 0.856 g of dichlorotetraamineplatinum to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0062] (2) preparing 50 mL of a 1 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0063] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 3 g of glycerol is added to carry out a cross-linking curing reaction for 7 hours to obtain material C;

[0064] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pt loading of the catalyst was 0.47 wt%.

[0065] Example 3

[0066] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1.5 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a potassium tetrachloroplatinate isopropanol solution containing 1.064 g of potassium tetrachloroplatinate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0067] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., and adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0068] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0069] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pt loading of the catalyst was 0.46 wt%.

[0070] Example 4

[0071] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a potassium tetrachloroplatinate isopropanol solution containing 1.064 g of potassium tetrachloroplatinate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0072] (2) Prepare 50 mL of a 2 wt % gelatin aqueous solution, heat and stir at 45° C. until completely dissolved, mix the gelatin aqueous solution with mixed solution B, continue stirring at 45° C., adjust the solution pH to 3.8 within 30 minutes, continue stirring and react for 75 minutes, and obtain mixed solution B.

[0073] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0074] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pt loading of the catalyst was 0.48 wt%.

[0075] Example 5

[0076] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a potassium tetrachloroplatinate isopropanol solution containing 1.064 g of potassium tetrachloroplatinate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0077] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., adjusting the solution pH to 4.7 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0078] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0079] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pt loading of the catalyst was 0.48 wt%.

[0080] Example 6

[0081] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a potassium tetrachloroplatinate isopropanol solution containing 0.532 g of potassium tetrachloroplatinate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0082] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., adjusting the solution pH to 3.8 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0083] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0084] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pt loading of the catalyst was 0.26 wt%.

[0085] Example 7

[0086] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a palladium nitrate dihydrate isopropanol solution containing 1.252 g of palladium nitrate dihydrate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0087] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., and adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0088] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 4 hours to obtain material C;

[0089] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pd loading of the catalyst was 0.52 wt%.

[0090] Example 8

[0091] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-scale silicon dioxide and a palladium chloride isopropanol solution containing 0.833 g of palladium chloride to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0092] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., and adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 75 minutes to obtain mixed solution B;

[0093] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 3 g of hydroxyethyl cellulose is added to carry out a cross-linking curing reaction for 5 hours to obtain material C;

[0094] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pd loading of the catalyst was 0.49 wt%.

[0095] Example 9

[0096] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.04 g of nano-scale silicon dioxide and a sodium chloropalladate isopropanol solution containing 1.388 g of sodium chloropalladate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0097] (2) Prepare 50 mL of a 1 wt% gelatin aqueous solution, heat and stir at 45° C. until completely dissolved, mix the gelatin aqueous solution with mixed solution B, continue stirring at 45° C., adjust the solution pH to 4.1 within 30 minutes, continue stirring and react for 75 minutes, and obtain mixed solution B.

[0098] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 10 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0099] (4) The material C was washed with an ethanol solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Pd loading of the catalyst was 0.48 wt%.

[0100] Example 10

[0101] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.03 g of nano-scale silicon dioxide and a hexaammineruthenium chloride isopropanol solution containing 1.532 g of hexaammineruthenium chloride to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0102] (2) Prepare 50 mL of a 2 wt % gelatin aqueous solution, heat and stir at 45° C. until completely dissolved, mix the gelatin aqueous solution with mixed solution B, continue stirring at 45° C., adjust the solution pH to 4.1 within 30 minutes, continue stirring and react for 75 minutes, and obtain mixed solution B.

[0103] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 10 g of hydroxyethyl cellulose is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0104] (4) The material C was washed with an acetone solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Ru loading of the catalyst was 0.47 wt%.

[0105] Embodiment 11

[0106] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 2 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.01 g of nano-scale silicon dioxide and a ruthenium nitrate isopropanol solution containing 1.569 g of ruthenium nitrate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0107] (2) preparing 50 mL of a 1 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., and adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 120 minutes to obtain mixed solution B;

[0108] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 6 g of glycerol is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0109] (4) The material C was washed with an acetone solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Ru loading of the catalyst was 0.51 wt%.

[0110] Example 12

[0111] (1) preparing 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 1 wt %, heating and stirring at 45° C. until completely dissolved, adding 0.02 g of nano-sized titanium dioxide and a ruthenium chloride isopropanol solution containing 1.024 g of ruthenium chloride trihydrate to the sodium carboxymethyl cellulose aqueous solution, and dispersing the mixture for 5 minutes using a homogenizer to obtain a mixed solution A;

[0112] (2) preparing 50 mL of a 2 wt % gelatin aqueous solution, heating and stirring at 45° C. until completely dissolved, mixing the gelatin aqueous solution with mixed solution B, continuing to stir at 45° C., and adjusting the solution pH to 4.1 within 30 minutes, and continuing to stir and react for 120 minutes to obtain mixed solution B;

[0113] (3) After the reaction is completed, the mixed solution B obtained in step (2) is placed in an ice water bath, and 2 g of hydroxyethyl cellulose is added to carry out a cross-linking curing reaction for 10 hours to obtain material C;

[0114] (4) The material C was washed with an acetone solution and then freeze-dried at -60°C for 12 hours to obtain the capsule-type metal catalyst. According to ICP test, the Ru loading of the catalyst was 0.49 wt%.

[0115] Example 13

[0116] Compared with Example 1, the difference in the preparation method of the capsule-type metal catalyst is that the amount of sodium carboxymethyl cellulose and gelatin is different. In this example, 50 mL of a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 3 wt% is used in step (1), and 50 mL of a gelatin aqueous solution with a mass concentration of 1 wt% is used in step (2), and the other conditions are the same, and the Pt loading of the prepared capsule-type metal catalyst is 0.48 wt%.

[0117] Embodiment 14

[0118] Compared with Example 1, the difference in the preparation method of the capsule-type metal catalyst is only that the amount of Pt metal salt used is different. In this example, a chloroplatinic acid hexahydrate isopropanol solution containing 0.105 g of chloroplatinic acid hexahydrate is added, and the other conditions are the same, and the Pt loading of the prepared capsule-type metal catalyst is 0.04 wt%.

[0119] Embodiment 15

[0120] Compared with Example 1, the difference of the preparation method of the capsule-type metal catalyst is that in step (2), the solution pH is different. In this embodiment, after the gelatin aqueous solution and the mixed solution B are mixed, the solution pH is adjusted to 3.8, and the other conditions are the same. The prepared capsule-type metal catalyst has a Pt loading of 0.41wt%.

[0121] Example 16

[0122] Compared with Example 1, the difference of the preparation method of the capsule-type metal catalyst is that in step (2), the solution pH is different. In this embodiment, after the gelatin aqueous solution and the mixed solution B are mixed, the solution pH is adjusted to 4.7, and the other conditions are the same. The prepared capsule-type metal catalyst has a Pt loading of 0.37 wt%.

[0123] Embodiment 17

[0124] Compared with Example 1, the difference of the preparation method of the capsule-type metal catalyst is that in step (2), the solution pH is different. In this embodiment, after the gelatin aqueous solution and the mixed solution B are mixed, the solution pH is adjusted to 3.6, and the other conditions are the same. The prepared capsule-type metal catalyst has a Pt loading of 0.07 wt%.

[0125] Embodiment 18

[0126] Compared with Example 1, the difference of the preparation method of the capsule-type metal catalyst is that in step (2), the solution pH is different. In this embodiment, after the gelatin aqueous solution and the mixed solution B are mixed, the solution pH is adjusted to 5.0, and the other conditions are the same. The prepared capsule-type metal catalyst has a Pt loading of 0.08 wt%.

[0127] Embodiment 19

[0128] Compared with Example 1, the difference in the preparation method of the capsule-type metal catalyst is that in step (3), the amount of curing agent is different. In this example, 1 g of glycerol is added, and the other conditions are the same, and the Pt loading of the prepared capsule-type metal catalyst is 0.35 wt%.

[0129] Comparative Example 1

[0130] Take 1g of carbon nanotubes as the carrier and as the mass standard, weigh H 2 PtCl 4 , ultrasonically dissolve in 1 mL of ultrapure water to obtain a Pt metal salt solution; add 1 g of carbon nanotubes to the metal Pt salt solution, stir with a glass rod to fully mix the carrier and the solution. After the impregnated catalyst precursor is aged at room temperature for 12 hours, it is transferred to a 120°C oven for drying for 12 hours. In a reducing atmosphere of pure hydrogen, it is reduced at 400°C for 4 hours to obtain a 1% Pt / CNT catalyst. According to ICP detection, the Pt loading of the catalyst is 0.96wt%.

[0131] Comparative Example 2

[0132] 100 mL of 0.4 mol / L Na 2 CO 3 The aqueous solution was added to a three-necked flask, and then the four metal salts H 2 PtCl 4 Mg(NO 3 ) 2 6H 2 O and Al(NO 3 )3 9H 2 O was dissolved in 100 mL of ultrapure water (referred to as solution E). In the ternary metal salt solution, the content of Pt was 1 wt%, and the content of Mg 2+ :Al 3+ The molar ratio is 3:1. At the same time, 250mL of a 0.4mol / L NaOH solution (called solution F) was also prepared. During the mixing process, the temperature was maintained at 65°C, the pH of the solution was maintained at 10±0.5, and solution E and solution F were slowly added to the three-necked flask at the same time and stirred vigorously. After the addition was completed, the temperature of the reaction solution was maintained at 65°C for 16 hours, and then it was filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. Finally, the sample was dried in still air at 100°C for 12 hours, and then immersed in 2mol / L Na 2 CO 3 The reaction was carried out in the solution for 16 hours. The sample obtained after filtration and drying was then reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Pt-LDH catalyst. The Pt loading of the catalyst was 0.98 wt% as determined by ICP.

[0133] Embodiment 20

[0134] Catalyst performance evaluation

[0135] 30 mg of the catalysts prepared in the above Examples 1 to 19 and Comparative Examples 1 to 2 and 3.5 mol of trimethoxysilane were added to the reactor, the reactor was sealed, and the air was purged with argon for several times. When the reaction temperature stabilized to the set value, ethylene was charged into the reactor, and stirring was started and timing was started. The stirring rate was 800 rpm, and the reaction temperature was 30 to 50 ° C and the pressure was 0.3 to 0.5 MPa. After 18 hours of reaction, sampling was performed and the samples were immediately analyzed by gas chromatography.

[0136] It should be noted that the product after the reaction was analyzed using an Agilent 6890N gas chromatograph, the chromatographic column used was HP-50 (15m×320um×0.25um), the carrier gas was nitrogen, and the detector was a flame ionization detector.

[0137] The catalytic performance of the catalyst of the present invention for preparing ethyltrimethoxysilane by the hydrosilylation reaction of ethylene and trimethoxysilane was evaluated by testing the trimethoxysilane conversion rate and ethyltrimethoxysilane selectivity and yield of the catalysts prepared in Examples 1 to 19 and the Pt / CNT and Pt-LDH catalysts.

[0138] Wherein: In the hydrosilylation reaction of ethylene and trimethoxysilane, the calculation formulas for the conversion rate of trimethoxysilane and the selectivity and yield of ethyltrimethoxysilane are as follows:

[0139] X(%)=(n 初始三甲氧基硅烷 -n 反应后三甲氧基硅烷 ) / n 初始三甲氧基硅烷 ×100%

[0140] S i (%)=(n 组分i ×A i ) / n 初始三甲氧基硅烷 ×100%

[0141] Y i (%) = X × S i ×100%

[0142] Wherein, X represents the conversion rate of trimethoxysilane, in %;

[0143] n 初始三甲氧基硅烷 、n 反应后三甲氧基硅烷 Respectively represent the amount of trimethoxysilane at the beginning and after the reaction, in mol;

[0144] S i It represents the selectivity of component i, in %;

[0145] n 组分i It represents the amount of substance of component i after the reaction, in mol;

[0146] A i Indicates the number of carbon atoms contained in the molecule of component i;

[0147] Y i It represents the yield of component i in %.

[0148] Table 1 Evaluation results of the hydrosilylation reaction of ethylene and trimethoxysilane using capsule-type metal catalysts

[0149]

[0150]

[0151] Since the hydrosilylation reaction will produce side reactions during the heating process, the prepared capsule-type catalyst wall material can be broken within the reaction temperature range to quickly release the active components. Table 1 shows that the results of Example 1 are better than those of Examples 15-18. This is mainly because the combination of gelatin and carboxymethyl cellulose requires a specific pH value. Beyond this range, it is not easy to form a capsule, which makes it difficult to load the active metal, thereby affecting the catalytic performance. Compared with Example 1 and Example 13, Example 1 performs better, which is related to the optimal ratio of gelatin and carboxymethyl cellulose. Different ratios will lead to differences in the mechanical properties of the capsule wall material, thereby affecting the process of catalytic activity release. Comparing Example 1 with Example 19, the results of Example 1 are also better. This is because the amount of curing agent is small, and the difficulty of forming a stable microcapsule catalyst is increased, while excessive use may cause the catalyst to adhere and be difficult to separate during freeze drying. In the hydrosilylation reaction of ethylene and trimethoxysilane, the capsule-type metal catalyst prepared by Example 1 has a conversion rate of trimethoxysilane exceeding 95%, and a selectivity of ethyltrimethoxysilane greater than 92%, which is significantly better than Pt / CNT and Pt-LDH catalysts.

[0152] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a capsule-type metal catalyst, characterized in that: The steps include: (1) preparing a sodium carboxymethyl cellulose aqueous solution of a certain concentration, and then adding an additive and a metal salt solution to the sodium carboxymethyl cellulose aqueous solution, and dispersing them uniformly to obtain a mixed solution A; (2) preparing a gelatin solution of a certain concentration, and mixing the gelatin solution and the mixed solution A uniformly, adjusting the pH of the solution to acidic and continuing the reaction to obtain a mixed solution B; (3) placing the mixed solution B obtained in step (2) in an ice water bath, and adding a curing agent to carry out a cross-linking curing reaction to obtain material C; (4) The material C is washed and dried to obtain the capsule-type metal catalyst.

2. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: In step (1), the additive is selected from one or more of nano-sized silicon dioxide and nano-sized titanium dioxide; and the metal salt solution is selected from one of Pt, Pd or Ru metal salt alcohol solutions.

3. The method for preparing a capsule-type metal catalyst according to claim 2, characterized in that: In step (1), the metal salt of Pd is selected from at least one of sodium chloropalladate, palladium chloride or palladium nitrate dihydrate; the metal salt of Pt is selected from at least one of chloroplatinic acid hexahydrate, potassium tetrachloroplatinate or tetraammineplatinum dichloride; and the metal salt of Ru is selected from at least one of ruthenium chloride, ruthenium nitrate or hexaammineruthenium chloride.

4. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: The mass ratio of sodium carboxymethyl cellulose to gelatin is 0.4-3.0; the added amount of the metal salt is 0.2-1.5 times the total mass of sodium carboxymethyl cellulose and gelatin; and the mass of the additive is 0.006-0.2 times the mass of the metal salt.

5. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: In step (2), pH=3.8-4.7, reaction temperature is 40-60°C, and reaction time is 0.5h-3.0h.

6. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: In step (3), the curing agent is selected from at least one of glycerol and hydroxyethyl cellulose; the added amount of the curing agent is 0.5 to 10 times the total mass of sodium carboxymethyl cellulose and gelatin.

7. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: In step (3), the curing and cross-linking reaction time is 4 to 10 hours.

8. The method for preparing a capsule-type metal catalyst according to claim 1, characterized in that: In step (4), the solvent used for washing is ethanol or acetone; the drying conditions are: -20°C to 80°C, freeze drying for 8 to 20 hours.

9. A capsule-type metal catalyst prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The metal loading is 0.05-2.0 wt%.

10. A use of the capsule-type metal catalyst according to claim 9, characterized in that: Used in hydrosilylation reactions.

Citation Information

Patent Citations

  • Method for preparing fluorine-containing electronic ink microcapsule

    CN101711966A

  • Method for preparing microcapsule taking hydrophobic substance as core material by complex coacervation method

    CN101857730A

  • Preparation method of pesticide microcapsule containing organic silicon

    CN104012528A

  • Preparation method of ethyltrimethoxysilane

    CN108864170A

  • Microcapsule catalyst, preparation method and applications thereof

    CN110903481A